Prediction of the Lightning Location for Transmission Systems using the characteristics of transient current waveform and travelling wave method - Prailkanok Lertwanitrot; Atthapol Ngaopitakkul; Sulee Bunjongjit (My University, 2015)
This paper proposes the travelling wave technique to predict the location of lightning on the transmission line. The conditions of lightning striking on the conductor of 115 kV Thailand's transmission line were simulated using ATP/EMTP program. The case studies were performed with changing various parameters such as inception angle, location of lightning, ground resistance of tower, amplitude of lightning strikes, and voltage level of transmission line, in order to evaluate the accuracy of the proposed technique. The characteristics of first peak time of current waveform are investigated as input data for travelling wave equation. The obtained results show that, the first peak time only tends to decrease with decreasing distance between the substation so that the lightning location can be calculated and gives a satisfactory accuracy.
Keywords: Lightning; Transient (computer programming); Transient analysis; Lightning and Electromagnetic Phenomena